The Influence of Motivation and Discipline on Teacher Performance at SDN Kemayoran 11 Pagi - Intan Rahmah Puspita; Dwi Rachmawati; Yuni Pambreni (Neo Journal of economy and social humanities, 2025)
In the era of globalization, organizational success is highly influenced by the quality of human resources, including in education. Teachers play a strategic role in ensuring effective learning. However, SDN Kemayoran 11 Pagi still faces issues with teacher discipline, especially in terms of inconsistent attendance and suboptimal performance in preparing and utilizing teaching modules based on the Merdeka Curriculum. Unlike many previous studies that measured teacher performance with general indicators, this research specifically evaluates teacher performance through the achievement of teaching modules in the Merdeka Curriculum, which reflects a more contextual and current standard of teacher competence. This study aimed to examine the effect of motivation and discipline on teacher performance. A quantitative approach was applied using saturated sampling, involving all 33 teachers at SDN Kemayoran 11 Pagi. Data were analyzed through multiple linear regression using SPSS. The results showed that motivation and discipline each had a positive and significant effect on teacher performance, both partially and simultaneously. The coefficient of determination indicated that 31.9% of the variation in teacher performance could be explained by motivation and discipline, while the remaining 68.1% was attributed to other factors. These findings imply that schools need to prioritize strategies that strengthen teacher discipline alongside motivation, as these aspects have been empirically proven to enhance teacher performance in implementing the Merdeka Curriculum.